Improving handover of patient care using a new weekend proforma with a focus on ceiling of care - Akhunbay-Fudge, Christopher Yusuf (BMJ Qual Improv Rep, 2014)
Patient handover is paramount for effective patient care and is often poorly documented or incomplete. North Bristol NHS Trust weekend handover proformas identify medical patients requiring weekend review. Many patients seen during on-call shifts are not handed over. Our aim was to develop Friday ward round proforma sheets for medical patients, to encourage clear documentation of management plans in order to improve handover of important information, particularly ceiling of care decisions. Questionnaires were completed by F1 doctors regarding current handover systems. Baseline data collected by on-call F1s included time of understanding a patient's ceiling of care decision, and difficulty of comprehension of medical notes. Repeat data were collected with novel proformas in situ. Multiple cycles were performed to refine the sheets and target problems arising in their use. Ninety-three percent of F1s wanted improved patient handover, with ceiling of care (87%) and management plans (73%) being the most difficult areas to understand. Time taken to ascertain ceiling of care decisions improved with the introduction of Friday handover proformas; mean time 153 seconds before and 5 seconds after. Clarity and documentation of management plans improved, with 50% improvement in ease of understanding medical notes. Results demonstrate that introducing Friday ward round proformas for medical patients improves communication between weekday and on-call teams, highlights current escalation of care plans, and leads to faster decision-making. Future plans include the introduction of a short educational session to the new F1 doctors and continued progress with introduction into hospital stationary.